2021
DOI: 10.1080/07448481.2021.1979009
|View full text |Cite
|
Sign up to set email alerts
|

Health and education concerns about returning to campus and online learning during the COVID-19 pandemic among US undergraduate STEM majors

Abstract: Objective: We examined undergraduate students' concerns about returning to campus and about online learning from home.Participants: Undergraduates majoring in STEM at US universities/colleges. Methods: Participants completed an online survey in July 2020. We content-analyzed responses to open-ended questions about concerns about Fall 2020.Results: Students (N=64) were 52% women, 47% low SES, and 73% races/ethnicities other than non-Hispanic white. Concerns about returning to campus included student noncomplian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
3
0
1
Order By: Relevance
“…Our work highlights the importance of an intersectional perspective in research related to the impact of the pandemic on STEM higher education. For example, research has found that STEM students had both health (e.g., mental health, socialization) as well as educational concerns (e.g., hands-on experiences; Palmer et al, 2021) but this research did not investigate these concerns with an intersectional perspective. The current work suggests that an intersectional framework may provide a nuanced understanding to student concerns and challenges during the pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…Our work highlights the importance of an intersectional perspective in research related to the impact of the pandemic on STEM higher education. For example, research has found that STEM students had both health (e.g., mental health, socialization) as well as educational concerns (e.g., hands-on experiences; Palmer et al, 2021) but this research did not investigate these concerns with an intersectional perspective. The current work suggests that an intersectional framework may provide a nuanced understanding to student concerns and challenges during the pandemic.…”
Section: Discussionmentioning
confidence: 92%
“…Durante el confinamiento también surgieron y tomaron fuerza diversas perspectivas sobre el regreso a la En esta misma línea, Nevaranta et al (2022) encontraron que la percepción de los alumnos sobre el aprendizaje en línea durante la pandemia es heterogénea, ya que algunos prefieren trabajar completamente en línea, mientras que otros prefieren la presencialidad, pues tienen serias dificultades con el aprendizaje remoto. En este sentido, la investigación de Palmer et al (2021) reveló que los estudiantes estaban preocupados por el regreso presencial al campus debido, entre otras causas, al incumplimiento de las medidas de prevención COVID-19 por parte de los estudiantes, el riesgo de infección y los planes inadecuados de las universidades para prevenir los contagios. Sin embargo, también mostraban preocupación por su aprendizaje en línea debido a la dificultad para concentrarse en las tareas escolares, la falta de desarrollo de competencias prácticas y las repercusiones negativas en sus interacciones sociales.…”
Section: Introductionunclassified
“…A study by Barber and colleagues (2021) found that compared to students with non-STEM majors, STEM students were less satisfied with the transition to online learning, reporting increased workload and decreased ability to participate in remote learning. Additionally, in a study investigating a population of undergraduate STEM majors, 26% of participants worried about quality of instruction upon returning to campus and 24% were concerned about the lack of hands-on learning and interactions with faculty during online learning (Palmer et al, 2021). These findings suggest that this adjustment was likely a source of stress for many undergraduate students.…”
Section: Introductionmentioning
confidence: 99%